2020
DOI: 10.1111/jocd.13673
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of efficacy of QR 678 and QR678 neo hair growth factor formulation for the treatment of female pattern alopecia in patients with PCOS—A prospective study

Abstract: Background Hair is an essential identity of women. Femininity, sexuality, attractiveness, and personality are symbolically linked to a woman’s hair. Female pattern hair loss is found in 20%‐30% of patients with polycystic ovary syndrome (PCOS). Aim The aim of the present study was to evaluate the efficacy of QR678® and QR678 Neo® therapy in the treatment of female alopecia with PCOS. Method A total of 20 females diagnosed with PCOS in the age 25‐50 years, with complaints of female pattern alopecia with Ludwig,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…Considerable decrease in hair fall was noted in 83% of the participants. Treatment was well tolerated by all patients 13‐17 …”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Considerable decrease in hair fall was noted in 83% of the participants. Treatment was well tolerated by all patients 13‐17 …”
Section: Discussionmentioning
confidence: 94%
“…A comparitive study of QR678 Neo ® with minoxidil and finasteride found that in advanced Alopecia, QR678 Neo ® may be more effective when given in combination with topical minoxidil and oral finasteride. All these studies have mentioned use of intradermal injection technique to deliver the formulation, and it showed a significant amount of benefit in all the parameters 12‐16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…QR678 Neo ® has growth factors such as vascular endothelial growth factor, basic fibroblast growth factor, insulin‐like growth factor‐1, keratinocyte growth factor, and copper tripeptide 1 or their biomimetic peptides which when administered into the scalp decreases the number of vellus hair, increases the terminal hair and hair shaft diameter. It also causes hair regrowth where the hair follicle is present but in dormant stage 12,13 …”
Section: Discussionmentioning
confidence: 99%
“…These agents are beneficial in controlling hair loss, but can only induce minimal new hair growth. 2 A new formulation, introduced by Kapoor and Shome in 2018 named QR678 Neo ® (US patent 2017, Indian Patent & Indian FDA approval 2019), is a plant-derived polypeptide solution which comprises of concentration of biomimetic peptides in a titrated manner. 3 QR678 Neo ® already proved its effectiveness in hair regrowth therapy for male and female pattern hair loss, and has also been to be more efficacious than PRP.…”
mentioning
confidence: 99%